ANALYSIS ON FINANCIAL PERFORMANCE OF JASA MARGA (PERSERO) TBK. BEFORE AND AFTER ACQUISITION - Ulina, Kezia Rahel; Pujiati, Desi (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to analyze the financial performance of Jasa Marga (Persero) Tbk before and after the acquisition using financial ratios, namely Cash Ratio, Net Profit Margin, Return On Equity, and Debt to Equity Ratio.. Design/methodology/approach- Financial data used for this research is from 2012 to 2018. The analysis is done by comparing the value of financial ratios before and after the acquisition with the value of industry standard financial ratios, and by comparing the average value of financial ratios before acquisition with the average value of financial ratios after acquisition. Findings- The results of industry standard analysis and comparative analysis before and after the acquisition show that financial performance measured through financial ratios decreases after acquisition Limitation- This research is inseparable from the limitations of time, funds, and theories controlled by the author. The company which is the object of research is Jasa Marga (Persero) Tbk through the Consolidated Financial Statement for the 2012-2018 period. Keywords: Financial Performance, Cash Ratio, Net Profit Margin, Return On Equity, Debt to Equity Ratio